An analysis of challenges of judicial management as a tool for resuscitating distressed companies: a case of Harare district - Gosha, Paul (Midlands State University, 2017)
The effects of recession has seen many companies in Zimbabwe going through financial distress. Having seen that the company is now under financial distress, the stakeholders seek methods of resuscitating their operations. The methods sought are either judicial management, bailout or scheme of arrangement. The main objective of this research was to analyze the challenges of judicial management as a resuscitation tool for distressed companies in Harare District. Literature in the field of judicial management was reviewed so as to examine the existing knowledge in this arena. Judicial management involves a lot of processes, which include looking for investors, downsizing human capital, selling major assets and negotiating with the debtors to defer payments. Judicial management is done by a judicial manager appointed by the court replacing the directors of the distressed company. Questionnaires and interviews were used to come up with primary data for the research. Convenience sampling was used in the selection of respondents. The research findings revealed that distressed organizations prefer judicial management to other resuscitation tools like bailout and scheme of arrangement. It was also found during the research that judicial management has some challenges like high judicial management fees. However, successful judicial management is possible when changes are made to the current Zimbabwe Companies Act (Chapter 24.03) thereby creating a strong base to judicial management processes.